Indicators of resource scarcity differentially moderate the impact of threat exposure on psychopathology in a cross-sectional community sample of youth - Larson, Eric R.; Moussa-Tooks, Alexandra B.; Wisner, Krista M. (Frontiers in Child and Adolescent Psychiatry, 2025)
Threat exposure and resource scarcity increase psychopathology risk throughout childhood and adolescence. However, it remains unclear whether these dimensions of early life adversity interact to impact psychopathology, whether different indicators of resource scarcity perform similarly in such interactions, and whether these relationships are similar between males and females. This analysis used a cross-sectional, multi-informant approach to investigate interactions between threat exposure and different indicators of resource scarcity (achievement-based, financial-based) for three major dimensions of psychopathology. Data are from 236 community-based non-help seeking youth aged 8-17 (M = 11.58, SD = 2.74) enrolled in the census-matched Nathan Kline Institute-Rockland Sample. Linear models were used to estimate interactions between threat exposure, and achievement-based scarcity (caregiver education and occupation) vs. financial-based scarcity (income-to-needs ratio), for major dimensions of psychopathology (internalizing, externalizing, thought disturbance). Linear models showed increasing threat exposure was associated with elevated internalizing and externalizing psychopathology symptoms, but not thought disturbance symptoms, when controlling for resource scarcity indicators. Achievement-based scarcity, but not financial-based scarcity, moderated these relationships, such that the impact of threat exposure on psychopathology depended on the level of caregiver achievement moreso than on the amount of familial financial resources. These patterns were similar in males (N = 132) and females (N = 104) when examined separately. Caregiver achievement may protect against symptoms of psychopathology in youth exposed to threat, suggesting that policies geared towards increasing education accessibility and job opportunities may have considerable downstream impact for child and adolescent well-being. Future work should explore interactions between adversity dimensions in population-based samples with greater variability in systems-level factors (e.g., neighborhood advantage).